Evaluasi Penerapan Pemungutan Pajak Kendaraan Bermotor (PKB) Melalui Layanan Samsat Keliling - Agusta Amanda Wulandari; Fransiscus Nicodemus Naiola (Univiversitas Dr. Djar Wattiheluw, 2023)
This research aims to find out how to evaluate the implementation of the SAMSAT Keliling service program to the receipt of motorvehicle taxes on UPTD. Pendapatan Daerah Wilayah Kota Kupang. This study is a qualitative descriptive study using primary and secondary data. The primary data in question is an interview conducted to find out more about the collection of motor vehicle taxes through SAMSAT Keliling, while the secondary data in question is the target data and realization of motor vehicle taxes in Kupang City in 2017-2020 obtained from UPTD. Pendapatan Daerah Wilayah Kota Kupang. Data analysis techniques in this study use the analysis of the Effectiveness of MOBILE SAMSAT through interviews and analysis of the effectiveness of PKB acceptance and the contribution of SAMSAT Roving then interpret it in the classification of effectiveness and contribution criteria. The results of this study the effectiveness rate of PKB receipts is effective and the effectiveness of motor vehicle tax collection through THE MOBILE SAMSAT service is effective and the contribution of motor vehicle tax revenue through THE SAMSAT Mobile service is very contributing during the last 4 (four) years i.e. 2017-2020.